Diction in Tarlingdut song lyrics by Anom Udin Zaen: Stylistic study - Esi Yulistiana; Sumarlam Sumarlam; Soediro Satoto (Universitas Islam Sultan Agung, 2019)
Song lyric is a mean to express the writer’s message publically. The message itself can be understood through understanding the writer’s diction (choice of words). This article concerns to Anom’s choices of words on his own ‘Tarlingdut’ song lyrics. This research aims to reveal Anom’s choice of words on his Tarlingdut song lyrics by using stylistic approach. The method used in this research is descriptive qualitative. Inventory report, repetitive and comprehensive reading, and record keeping are techniques used to collect the data. The result shows that Anom’s choice of words in his nine song lyrics is aesthetic and unique. The result of the research is expected to make some contribution in understanding Tarlingdut songwriters’ choice of words to express their ideas.